2008
DOI: 10.1089/acm.2006.6344
|View full text |Cite
|
Sign up to set email alerts
|

The Mushroom Agaricus blazei Murill Extract Normalizes Liver Function in Patients with Chronic Hepatitis B

Abstract: Background: Hepatitis B is a global health problem. Use of complementary and alternative medicine has been popular among patients with hepatitis B. This 1-year open-label pilot study aims to observe whether Agaricus blazei Murill extract improves liver function in patients with hepatitis B.Methods: This study involved 12 months of clinical observation. Four (4) patients with hepatitis B who met the criteria (1) aged between 20 and 65 years; (2) being Chinese; (3) having been a hepatic B carrier (HBAg(ϩ)) for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 12 publications
4
28
0
2
Order By: Relevance
“…These results corroborate those of Hsu et al (2008) and Wu et al (2011), who found that treatment with A. blazei was led to decreased ALT activity in patients with chronic diseases and rats treated with carbon tetrachloride. On the other hand, Chang et al (2012) found an increase in ALT in experiments with female mice treated with A. blazei.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results corroborate those of Hsu et al (2008) and Wu et al (2011), who found that treatment with A. blazei was led to decreased ALT activity in patients with chronic diseases and rats treated with carbon tetrachloride. On the other hand, Chang et al (2012) found an increase in ALT in experiments with female mice treated with A. blazei.…”
Section: Resultssupporting
confidence: 91%
“…Treatments with A. blazei extracts have been shown to lead to AST decreases in mice with hepatotoxicity induced by carbon tetrachloride (WU et al, 2011) and in human patients with hepatitis B (HSU et al, 2008). Similarly, a decrease AST was observed for patients with colorectal cancer treated with Agaricus sylvaticus post operatively (COSTA FORTES; GARBI NOVAES, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the concentration and quality of dietary fiber component present in the composition of the mushroom A. brasiliensis significantly reduce absorption and utilization of important lipid fractions carried by the diet (Hsu, Hwang, Chiang, & Chou, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides are the most important for modern nutrition and medicine, whilst -glucan is the best known and the most versatile metabolite with a wide spectrum of biological activities (Chang & Wasser, 2012). Studies conducted on rats have demonstrated effective action of the bioactive compounds found in the genus Agaricus macrofungi on the liver tissue, especially as protective factors of cell types whose activity is essential for the metabolism of fatty acids and other organic biomolecules (Hsu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is also used as antimutagenic, antioxidant, and as immune stimulator [10]. Some studies report the antiviral activity of extracts and compounds from mycelium or fruiting body of A. brasiliensis at replication of poliovirus (PV), Western equine encephalitis (WEE), Hepatitis B (HBV) and C (HCB) virus and HSV-1 and HSV-2 [11][12][13][14][15][16]. The aim of the present study was to investigate the antiviral activity of an A. brasiliensis polysaccharide, its fractions, as well as, its carboxymethylated and sulfated derivatives in the replication of HSV-1 and BoHV-1.…”
Section: Introductionmentioning
confidence: 99%